2021
DOI: 10.1039/d1em00060h
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigator series: chemical and physical properties of organic mixtures on indoor surfaces during HOMEChem

Abstract: Organic films on indoor surfaces serve as a medium for reactions and for partitioning of semi-volatile organic compounds and thus play an important role in indoor chemistry. However, the chemical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 69 publications
0
34
0
Order By: Relevance
“…Decreasing median C* by nearly an order of magnitude during Thanksgiving compared to background levels has strong implications toward the propensity of indoor VOCs to partition to condensed phases, and thus, their eventual fates and lifetimes indoors. We speculate that lower-volatility Thanksgiving emissions enhanced organic grime layers/films on indoor surfaces relative to other experimental periods …”
Section: Results and Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Decreasing median C* by nearly an order of magnitude during Thanksgiving compared to background levels has strong implications toward the propensity of indoor VOCs to partition to condensed phases, and thus, their eventual fates and lifetimes indoors. We speculate that lower-volatility Thanksgiving emissions enhanced organic grime layers/films on indoor surfaces relative to other experimental periods …”
Section: Results and Discussionmentioning
confidence: 81%
“…We speculate that lower-volatility Thanksgiving emissions en-hanced organic grime layers/films on indoor surfaces relative to other experimental periods. 47 Results in Figure 4a,b show the chemical complexity of Thanksgiving VOC emissions compared to stir-frying. The indoor air composition during Thanksgiving was drastically altered by a multitude of VOCs spanning a wide range of volatilities (log 10 C* = 2−11+) and carbon numbers (nC = 1− 10).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The particles from the stir-fry event correspond with NaNA, with most prevalent vibrational modes around 1570, 1560 and 1460, 1450 cm –1 corresponding to ν as (COO – ) and ν s (COO – ), respectively. O’Brien et al found that in material extracted from HOMEChem glass samples, CC bonds were still present and susceptible to further oxidation . These moieties are expected around 1650 cm –1 and subsequently would spectrally overlap with the carboxylate modes observed.…”
Section: Resultsmentioning
confidence: 99%
“…Organic films and particles containing unsaturated lipids are ubiquitous indoors. Examples include human skin oil films and cooking oil films and particles. Human skin oil films are ubiquitous on indoor occupants and also form when occupants touch indoor surfaces. Skin oil is mainly produced by the sebaceous gland, serving as a natural protector against microorganisms and helping to retain water in the human body .…”
Section: Introductionmentioning
confidence: 99%
“…The typical thickness of skin oil films can range from less than 0.5 μm in sebum-poor extremities to greater than 4 μm in sebum-rich areas . Cooking oil films are formed by spillage or splashing during food preparation and deposition of aerosol particles formed during cooking. , As a result of these various processes, cooking oil deposits are variable in their spatial extent, ranging from individual particles to continuous films with typical thicknesses in the micron-size range, depending on the deposition (collection) time …”
Section: Introductionmentioning
confidence: 99%